Exploring Migrant Employees’ Experiences of Workplace Integration and Well-being: Insights from MNCs Operating in Finland - Amin, Syed Mohammed Zahid Ibne (My University, 2024)
As globalization has pushed workforce diversity, MNCs in Finland employ a growing number of migrants, and these employees often face challenges related to language barriers, cultural differences, and social isolation, which can impact their overall well-being and sense of belonging. These aspects are core interests of this study, which explores the workplace integration and well-being of migrant employees within multinational corporations (MNCs) operating in Finland. This study examined how organizational practices and workplace culture affect migrant employees’ integration and well-being based on Social Identity and Organizational Support theories. A qualitative approach was employed with semi-structured interviews to gather personal perceptions from migrant employees in Finnish workplaces about their integration and well-being experiences and the role of organizational support if there is any. It is found that supportive organizational practices, including language assistance, mentorship programs, and cultural orientation initiatives promote inclusion and enhance well-being. Social Identity Theory helps explain the importance of a strong sense of belonging, where migrant employees feel they are part of the team as well as the organization, which is further strengthened by Organizational Support Theory's emphasis on perceived support from the organization. The study reveals that when migrant employees feel valued and supported by their organization and team, they experience better integration, improved well-being, and a stronger connec-tion to the workplace. Findings concluded as recommendation that having regular mentorship and peer support networks is important for building strong relationships and a sense of belonging within the company. Also, creating ways for migrant employees to give feedback on their challenges and needs can make their experience better, showing them they are valued and supported. To keep inclusion efforts going effective, the study suggests that companies should focus on diversity and inclusion training for everyone. This helps create an empathetic and supportive workplace culture. By adopting these strategies, MNCs operating in Finland can create a more inclusive environment that boosts the well-being of migrant employees and improves overall team cohesion and performance. It is to be noted that this research is limited by its focus on a single country with a limited sample, which may affect the generalizability of the findings. More research could explore the integration and well-being of migrant employees in various cultural and organizational contexts and examine the role of specific organizational practices across different types of workplaces in Finland. Further studies would provide a deeper comprehension of the factors that enhance the inclusion and satisfaction of migrant employees globally.
Keywords: employees; immigrants; well-being at work; well-being; integration of migrants; workplace culture; migrant integration; migrants; multiculturalism; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business